(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the pedagogical foundations for developing the psychological readiness of athletes in track and field training sessions within the context of higher pedagogical sports education. Psychological readiness is interpreted as an integral component of sports mastery that combines emotional stability, self-regulation, motivation, confidence, attention control, volitional effort, and the ability to perform effectively under competitive and training stress. In track and field, where athletes face high individual responsibility, repeated performance evaluation, strict time and distance criteria, and the need for technical precision, psychological preparation becomes a decisive factor in achieving stable results. The article argues that the development of psychological readiness should not be treated as an isolated auxiliary task but as a pedagogically organized and systematically embedded process integrated into daily training. The study highlights the importance of coach-athlete interaction, goal setting, reflective practice, positive feedback, situational modeling, and individualized pedagogical support in shaping athletes’ psychological competence. Special attention is given to the role of training environments that promote self-confidence, discipline, resilience, concentration, and stress tolerance. The article also considers how pedagogical methods can be adapted to the age, qualification, specialization, and emotional characteristics of student-athletes in pedagogical universities. It is concluded that the purposeful development of psychological readiness in track and field training enhances training effectiveness, improves competitive consistency, supports personal growth, and contributes to the formation of future sports professionals who are capable of maintaining both high performance and psychological balance.